Sociomotor interaction techniques in the development of body expression in primary school students - Jimenez Cueva, Alex Ylde (2018)
The objective of the present investigation was to determine the effects of the sociomotor interaction techniques on the corporal expression in students of a particular educational institution of the Rímac, 2016 and it arises in response to the problems presented in the educational institution regarding the development of one of the dimensions of the area of physical education obeying a quantitative design of experimental type and using as a data collection instrument a checklist, in a sample of 30 students. The results obtained indicated that the techniques of socio-motor interaction have an effect on the development of body expression, according to the Wilcoxon signedrank test (, 002 ≤, 05), thus concluding that if the students work with the techniques then they will develop your body expression.